Effects of initial graft tension on clinical outcome after anatomic double-bundle anterior cruciate ligament reconstruction: comparison of two graft tension protocols. Issue 1 (December 2016) - Kondo, Eiji; Yasuda, Kazunori; Kitamura, Nobuto; Onodera, Jun; Yokota, Masashi; Yagi, Tomonori; Iwasaki, Norimasa
Abstract Background In anatomic double-bundle anterior cruciate ligament (ACL) reconstruction, there are great controversies concerning the ideal graft tension protocols. The purpose of this study was to clarify differences in the effect of two graft tension protocols on the clinical outcome after anatomic double-bundle anterior cruciate ligament (ACL) reconstruction by comparing the minimum 2-year clinical results. Methods Ninety-seven patients with unilateral anatomic double-bundle ACL reconstruction were divided into two groups. In the first 44 patients (Group I), a 40-N tension was applied to each of the two hamstring autografts at 30° of knee flexion, and simultaneously fixed onto the tibia. In the remaining 53 patients (Group II), a 30-N tension was applied to each graft at 10° of knee flexion, and simultaneously fixed onto the tibia. Each patient was examined 2 years after surgery. Results There wasn't a significant difference in the background of the two groups. There was no significant difference in the postoperative anterior laxity between the two groups. The average was 1.1 mm and 0.9 mm in Groups I and II, respectively. There wasn't any differences between the two groups in Lysholm knee score, International Knee Documentation Committee (IKDC) evaluation and muscle strength. Four patients had loss of knee extension in a range of 5° and 10° in Group I and none of the patients in Group II exhibited any loss in knee extension; which was statistically significant (p  = 0.025). Conclusion The two initial graft tension protocols did not result in any significant differences in the Lysholm knee score and IKDC grade. However, it was noted that the 40-N tension applied to each graft at 30° of knee flexion more significantly induced loss of knee extension in comparison to the 30-N tension applied to each graft at 10°. From a clinical viewpoint, the loss of knee extension is one of the pathological conditions that should be absolutely avoided after ACL reconstruction. Therefore, the 30-N tension applied to each graft at 10° is preferable to the other graft tension protocol.